Cutaneous Squamous Cell Carcinoma: Review of the Eighth Edition of the American Joint Committee on Cancer Staging Guidelines, Prognostic Factors, and Histopathologic Variants. (July 2017) - Motaparthi, Kiran; Kapil, Jyoti P.; Velazquez, Elsa F.
Abstract : Cutaneous squamous cell carcinoma is the second most common form of nonmelanoma skin cancer after basal cell carcinoma and accounts for the majority of nonmelanoma skin cancer–related deaths. In 2017, the American Joint Committee on Cancer revised the staging guidelines of cutaneous squamous cell carcinoma to reflect recent evidence concerning high-risk clinicopathologic features. This update reviews the literature on prognostic features and staging, including the eighth edition of the American Joint Committee on Cancer Staging Manual. A wide range of histopathologic variants of cutaneous squamous cell carcinoma exists, several of which are associated with aggressive behavior. A review of cutaneous squamous cell carcinoma variants, emphasizing diagnostic pitfalls, immuhistochemical findings and prognostic significance, is included. Of note, the eighth edition of the American Joint Committee on Cancer Staging Manual refers to squamous cell carcinoma of the head and neck only.